The Use of WhatsApp in the Learning Process among Graduate Students in the University of Nairobi, Kenya - K. O., Evans (African Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to evaluate the use of WhatsApp in the learning process among graduate students in the University of Nairobi. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the use of WhatsApp in the learning process among graduate students in the University of Nairobi. Preliminary empirical review reveals that there is no doubt that digital technology is of significance in education today. WhatsApp mobile technology is extremely valuable in this regard, as it is widely and extensively employed in online university education. It also provides students with more options and possibilities in the context of online learning. Almost everything in the world has gone digital. Unique Contribution to Theory, Practice and Policy: The Social Constructivism theory and Activity theory may be used to anchor future studies on the use of WhatsApp in the learning process among graduate students in the University of Nairobi. There is need for a quantitative survey to establish the statistical significance effect of the use of WhatsApp as a method of learning for graduate school students. There is also need for a comparative study on the effectiveness of the use of WhatsApp in learning and traditional form of learning